Internationalization strategies – A study case for Portuguese firms - Pereira, Raquel (2018)
Internationalization remains widely debated as it is seen as a key strategy for the competitiveness of companies and economies. In the Portuguese context, where there has been a favorable and sustained evolution of exports for several years, the internationalization and diversification of markets seems to play a fundamental role for the sustainability of companies.Following a qualitative methodology, our goal is to analyze the internationalization process of three SMEs to find out how they approach the international markets. The results suggest some evidence concerningthe usefulness of the reviewed literature. They indicate that Uppsala model is useful to understand part of the SMEs IP. However, they also indicate that some firms begin their IP very quickly todispersed markets, diverging from some of the principles of the Uppsala model. For thefirms under study, exporting is the main strategy or entry mode in the external markets and the reasons to begin the IP are related to factors such as the manager’s profile, the business model and the networks which the company may be a part of.